2006
DOI: 10.1111/j.1472-8206.2006.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammation by PPARs: a future approach to treat lung inflammatory diseases?

Abstract: Lung inflammatory diseases, such as acute lung injury (ALI), asthma, chronic obstructive pulmonary disease (COPD) and lung fibrosis, represent a major health problem worldwide. Although glucocorticoids are the most potent anti-inflammatory drug in asthma, they exhibit major side effects and have poor activity in lung inflammatory disorders such as ALI or COPD. Therefore, there is growing need for the development of alternative or new therapies to treat inflammation in the lung. Peroxisome proliferator-activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
120
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(122 citation statements)
references
References 187 publications
1
120
0
1
Order By: Relevance
“…Previous studies have suggested that PPAR-c ligands reduce the expression of inflammatory cytokine genes and the production of inflammatory cytokines [11,12]. Consequently, PPAR-a and PPAR-c agonists may be helpful in the treatment of acute inflammatory diseases, such as ALI [13]. In this context, several studies have proven a beneficial role for PPAR-c agonists in models of allergic airway inflammation and bleomycin-induced ALI [14,15].…”
mentioning
confidence: 99%
“…Previous studies have suggested that PPAR-c ligands reduce the expression of inflammatory cytokine genes and the production of inflammatory cytokines [11,12]. Consequently, PPAR-a and PPAR-c agonists may be helpful in the treatment of acute inflammatory diseases, such as ALI [13]. In this context, several studies have proven a beneficial role for PPAR-c agonists in models of allergic airway inflammation and bleomycin-induced ALI [14,15].…”
mentioning
confidence: 99%
“…Furthermore, it has been demonstrated that activating PPAR␥ in the absence of IL-4 and IL-13 is sufficient to drive M2 qualities in macrophages [58], suggesting it may play an independent role in alternative activation. In particular, the activation of these factors appears to be essential for the regulation of pulmonary inflammation by lung macrophages and may represent a crucial regulatory component capable of shifting lung macrophages to a protective phenotype [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that fibrates affected the virus titres. It is known that both PPAR-a and PPAR-c agonists have anti-inflammatory and immunomodulatory activities, and several investigators have suggested that they might be used to treat acute lung injury (Becker et al, 2006;Cuzzocrea, 2006;Paola & Cuzzocrea, 2007). One study showed that glitazones (PPAR-c agonists) inhibit respiratory syncytial virus infection in human lung epithelial cells, probably by inhibiting viral gene expression and not earlier adhesion or fusion processes (Arnold & König, 2006).…”
Section: /Cd8mentioning
confidence: 99%